2013
DOI: 10.2214/ajr.12.10393
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Number and Associated Costs of Unindicated Dual-Phase Head CT Examinations After a Quality Improvement Initiative

Abstract: 1049ward referring clinicians and other health care providers in an effort to optimize patient care in radiology [1,2].In this study, we performed a quality improvement initiative with the goal of reducing the number of unindicated dual-phase head CT examinations by educating referring physicians and radiology faculty about the ACR Appropriateness Criteria. Previous quality initiative studies involving clinical decision support in radiology have focused on either volume reduction [3][4][5] or adherence to ACR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
(17 reference statements)
0
9
0
3
Order By: Relevance
“…Four studies reported on radiation frequency reduction, one in the "dose-feedback system" category Duke 2012 [23], and three in the "provision of training" category Bussieres 2013 [24]. Stein 2010 [21], and Strother 2013 [25] (Figure 3). Studies were heterogeneous in terms of outcome metrics, study design, and technology used.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported on radiation frequency reduction, one in the "dose-feedback system" category Duke 2012 [23], and three in the "provision of training" category Bussieres 2013 [24]. Stein 2010 [21], and Strother 2013 [25] (Figure 3). Studies were heterogeneous in terms of outcome metrics, study design, and technology used.…”
Section: Resultsmentioning
confidence: 99%
“…Additional adherence to appropriate imaging recommendations through collaborative efforts among radiologists and ordering physicians is needed. Physician education, standardization of order entry, and establishment of decision support systems have emerged as management strategies [29] demonstrating reduction in imaging overutilization and costs [30][31][32]. Evidence-based imaging is also promoted by the Protecting Access to Medicare Act of 2014 [33], which calls for the establishment and frequent review of appropriate use criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although the process ends at the report finalization in this study, the entire process can be extended to include the billing and coding activities and dealing with denial of payment. We did not address the appropriateness of CT examinations in this study (6,(35)(36)(37). Similarly, we did not address outcomes or quality of care under CT study to estimate value of care.…”
Section: Discussionmentioning
confidence: 98%